- #1

- 245

- 6

(1) Given: b

(2) Suppose: a

(3) By implication with (2) and (1), a→b

I just saw this proof.... And, I don't understand why this is true. How am I supposed to think about problems like this one?

Edit:

Here's another one:

The only steps here I understand are 1 to 5. I don't know why 6 and 7 are true.(1) Given: (p∧q)→r

(2) Suppose: p

(3) Suppose: q

(4) By conjunction with (2) and (3), p∧q.

(5) By MP with (1) and (4), r

(6) By implication with (3) and (5), (q→r)

(7) By implication with (2) and (6), p→(q→r)